1996
DOI: 10.1021/jm950807f
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Antagonist Activity of Naltrexone-Derived Bivalent Ligands:  Importance of a Properly Oriented Molecular Scaffold To Guide “Address” Recognition at κ Opioid Receptors

Abstract: The presence of a molecular scaffold to orient a basic group is important for potent and selective kappa opioid antagonist selectivity. An attempt to determine how the geometry of the scaffold affects this selectivity has led to the synthesis of a bivalent ligand (5) whose linker constrains the N17' basic nitrogen (the "address") to a position that is 6.5 A from N17' in the kappa antagonist norBNI (1) when these molecules are superimposed. The fact that compound 5 was found to be a highly selective and potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Similar results are seen with the hydrazide series as well. Thus, these agents do not simultaneously label two binding pockets, and their mechanism(s) of prolonged activity differ from that proposed by Portoghese for his bivalent ligands (Erez et al, 1982;Portoghese et al, 1986;Bolognesi et al, 1996).…”
Section: Mu Antagonistsmentioning
confidence: 72%
“…Similar results are seen with the hydrazide series as well. Thus, these agents do not simultaneously label two binding pockets, and their mechanism(s) of prolonged activity differ from that proposed by Portoghese for his bivalent ligands (Erez et al, 1982;Portoghese et al, 1986;Bolognesi et al, 1996).…”
Section: Mu Antagonistsmentioning
confidence: 72%
“…This suggested that the decahydroisoquinoline moiety within the second pharmacophore of norBNI acts as a scaffold to rigidly hold and direct its N17′ basic nitrogen to a subsite that is unique to the kappa receptor. Given that an analog of norBNI, with an isosteric thiophene [13] in place of the pyrrole moiety, possesses binding selectivity similar to that of norBNI, and the finding that a bivalent ligand whose scaffold geometry differs substantially from that of norBNI are not kappa-selective [14], supports the important directive role of the scaffold. Consequently, the binding of norBNI to the kappa receptor was postulated to involve two major subsites: The first subsite recognizes one of the antagonist pharmacophores, while the second subsite containing an anionic group associates with the cationic protonated N-17′ moiety in the second half of the molecule.…”
Section: Molecular Recognition Of Norbinaltorphimine At the Kappa Opimentioning
confidence: 92%
“…This compound distributes into the peripheral nervous system with low central nervous system bioavailability. 93 CTOP (47) 94,95…”
Section: -Selective Agonists and Antagonistsmentioning
confidence: 99%
“…A morphinan derivative, TRK-820 (92), exhibits high potency and k selectivity over m and d receptors. This k selective agonist shows over 85-fold stronger analgesic activity than those of morphine and U50488H (93). 171 The 6 0 -guanidinium naltrindole (6 0 -GNTI (94)) is a potent k opioid receptor selective agonist.…”
Section: K-selective Agonists and Antagonistsmentioning
confidence: 99%